Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the set of all points that are equidistant from the line [tex]\( y = 1 \)[/tex] and the point [tex]\((0, 3)\)[/tex], let's follow these steps:
1. Express the distance from a point [tex]\((x, y)\)[/tex] to the line [tex]\(y = 1\)[/tex]:
- For the line equation [tex]\(y - 1 = 0\)[/tex], the general formula for distance from a point [tex]\((x_1, y_1)\)[/tex] to a line [tex]\(Ax + By + C = 0\)[/tex] is given by:
[tex]\[ \text{Distance} = \frac{|Ax_1 + By_1 + C|}{\sqrt{A^2 + B^2}} \][/tex]
- Here the line [tex]\(y - 1 = 0\)[/tex] implies [tex]\(A = 0\)[/tex], [tex]\(B = 1\)[/tex], and [tex]\(C = -1\)[/tex]. The distance from a point [tex]\((x, y)\)[/tex] to this line simplifies to:
[tex]\[ \text{Distance} = \frac{|0 \cdot x + 1 \cdot y - 1|}{\sqrt{0^2 + 1^2}} = |y - 1| \][/tex]
2. Express the distance from a point [tex]\((x, y)\)[/tex] to the point [tex]\((0, 3)\)[/tex]:
- The distance between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
- For our points [tex]\((x, y)\)[/tex] and [tex]\((0, 3)\)[/tex], the distance is:
[tex]\[ \text{Distance} = \sqrt{(x - 0)^2 + (y - 3)^2} = \sqrt{x^2 + (y - 3)^2} \][/tex]
3. Set the distances equal to each other:
- We are looking for the points where the distance from [tex]\((x, y)\)[/tex] to the line [tex]\(y = 1\)[/tex] is equal to the distance from [tex]\((x, y)\)[/tex] to the point [tex]\((0, 3)\)[/tex]:
[tex]\[ |y - 1| = \sqrt{x^2 + (y - 3)^2} \][/tex]
Thus, the equation representing the set of all points that are equidistant from the line [tex]\(y = 1\)[/tex] and the point [tex]\((0, 3)\)[/tex] is:
[tex]\[ \boxed{\text{Eq} (|y - 1|, \sqrt{x^2 + (y - 3)^2})} \][/tex]
1. Express the distance from a point [tex]\((x, y)\)[/tex] to the line [tex]\(y = 1\)[/tex]:
- For the line equation [tex]\(y - 1 = 0\)[/tex], the general formula for distance from a point [tex]\((x_1, y_1)\)[/tex] to a line [tex]\(Ax + By + C = 0\)[/tex] is given by:
[tex]\[ \text{Distance} = \frac{|Ax_1 + By_1 + C|}{\sqrt{A^2 + B^2}} \][/tex]
- Here the line [tex]\(y - 1 = 0\)[/tex] implies [tex]\(A = 0\)[/tex], [tex]\(B = 1\)[/tex], and [tex]\(C = -1\)[/tex]. The distance from a point [tex]\((x, y)\)[/tex] to this line simplifies to:
[tex]\[ \text{Distance} = \frac{|0 \cdot x + 1 \cdot y - 1|}{\sqrt{0^2 + 1^2}} = |y - 1| \][/tex]
2. Express the distance from a point [tex]\((x, y)\)[/tex] to the point [tex]\((0, 3)\)[/tex]:
- The distance between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] is given by:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
- For our points [tex]\((x, y)\)[/tex] and [tex]\((0, 3)\)[/tex], the distance is:
[tex]\[ \text{Distance} = \sqrt{(x - 0)^2 + (y - 3)^2} = \sqrt{x^2 + (y - 3)^2} \][/tex]
3. Set the distances equal to each other:
- We are looking for the points where the distance from [tex]\((x, y)\)[/tex] to the line [tex]\(y = 1\)[/tex] is equal to the distance from [tex]\((x, y)\)[/tex] to the point [tex]\((0, 3)\)[/tex]:
[tex]\[ |y - 1| = \sqrt{x^2 + (y - 3)^2} \][/tex]
Thus, the equation representing the set of all points that are equidistant from the line [tex]\(y = 1\)[/tex] and the point [tex]\((0, 3)\)[/tex] is:
[tex]\[ \boxed{\text{Eq} (|y - 1|, \sqrt{x^2 + (y - 3)^2})} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.